Problems following topic shift in interactions with repaired cleft children - Saad, Mohammad Azannee; Jariah, Mohd Jan; Wahid, Ridwan (Universitas Pendidikan Indonesia, 2020)
Children with a history of cleft lip and/or palate (CL/P) can experience a range of difficulties such as sound articulation errors and reduced psychosocial functioning. This causes interaction with them to contain more frequent communication breakdowns than non-cleft children. The present study shows evidence of such breakdowns involving topic shifts in the interaction between parents and their repaired CL/P children. Interactional data were obtained through a series of recordings of three parent-child sets. The process is guided by the framework of Conversation Analysis (CA) while coding of topic shift adopts Crow’s typology (1983). Findings show that topic shift during interaction can indeed cause problems for children with a history of cleft, especially involving palatal cleft. Specifically, through the children’s repair initiations, the problems are manifest when a topic is introduced once the previous topic concludes, when a topic is extended and when a topic is revisited. This study shows that topic shift can potentially be a source of problems to CL/P children. Findings are useful for speech therapists, parents and teachers.